Productive and Nutritional Characteristics of Native Grasses from the Floodplain Banks Ecosystem in the Colombian Orinoquia (2022)
Productive and nutritional evaluations of native grasses are usually scarce, limiting their use in the feeding of herbivorous species. This study aims to determine the forage yield and nutritional value of native grasses from the floodplain “banks” ecosystem in the Colombian Orinoquia. Four native grasses (Paspalum plicatulum, Axonopus compresus, Axonopus purpussi, and Paspalum spp.) and a “control” grass (introduced Brachiaria hybrid cv. Mulato) were sown and sampled at 30, 40, and 50 days of age. On each sampling date, biomass production in a 1 m2 frame was estimated, and the chemical composition was analyzed using near-infrared spectroscopy. Data analysis included repeated measures analysis, correlations, and multiple linear regression. The grasses’ nutritional characteristics varied as follows: dry matter (DM, 0.9–2.5 ton/ha), crude protein (CP, 4.3–10.2%), neutral detergent fiber (NDF, 61–73.9%) ash (3.2–8.7%), and dry matter digestibility (DMD, 50.8–56.3%). P. plicatulum achieved comparable forage production to that of the “control” grass. A. purpussi, Paspalum sp., and P. plicatulum presented similar CP and ash contents, and a higher Ca:P ratio. Regression analysis indicated that DMD was affected by the CP and acid detergent fiber (ADF) levels. These native grasses constitute promising nutritional alternatives that must be considered in the region’s livestock-production system